2011
DOI: 10.3151/jact.9.251
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Methods to Detect and Quantify Damage in Restrained Concrete Ring Specimens

Abstract: This paper describes the use of three experimental methods to detect shrinkage cracking in restrained ring specimens. These methods include monitoring the strain at the inner surface of the restraining steel ring, using passive acoustic emission, and measuring the electrical resistance of conductive materials that are applied to the surface of the mortar. The methods for detecting cracking are compared and their advantages and limitations are discussed. Both plain and steel fiber reinforced (2% steel fiber by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…5 Conductive surface sensors have been recently developed for crack detection in both one-and twodimensional (1D and 2D) settings. 1D sensors are usually made of strips of conductive materials, [5][6][7][8][9][10][11][12][13] while a 2D sensor (also referred to as a sensing skin) consists of a patch of conductive material and an array of electrodes on the patch perimeter. [14][15][16][17][18][19][20][21] While the above-mentioned 2D sensors use EIT to reconstruct the spatial conductivity (or resistivity) distribution, other types of 2D sensors have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…5 Conductive surface sensors have been recently developed for crack detection in both one-and twodimensional (1D and 2D) settings. 1D sensors are usually made of strips of conductive materials, [5][6][7][8][9][10][11][12][13] while a 2D sensor (also referred to as a sensing skin) consists of a patch of conductive material and an array of electrodes on the patch perimeter. [14][15][16][17][18][19][20][21] While the above-mentioned 2D sensors use EIT to reconstruct the spatial conductivity (or resistivity) distribution, other types of 2D sensors have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the deformation near the curved edges is particularly important in mechanical or failure analyses. For example, for a ring component under diametrical compression, cracks initiate from the hole edge owing to the local stress concentration [5]. From this perspective, the accurate measurement of deformations near or on the curved edges of specimens or structures plays a very important role in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Raoufi et al [30] compared the performance of these 1D conductive surface sensors in crack detection with acoustic emission and image analysis techniques during shrinkage cracking tests, and used these sensors as a method to study the effect of the bonded substrate length on crack opening. Previous studies [30,31] have shown that the time of visible cracking is captured accurately by conductive surface materials. Recently, more advanced methods such as radio frequency identification [32] and frequency selective circuits (FSC) [33] have been used in conjunction with these 1D conductive surface sensors for damage detection in concrete materials and reinforced concrete elements.…”
Section: Introductionmentioning
confidence: 99%